Exil et diaspora au prisme d’une bibliothèque arménienne au xxe siècle - Boris Adjemian (Diasporas: Circulations, Migrations, Histoire)
What is the meaning of studying the history of an Armenian librarian and his books in Paris during the interwar period, and their fate under German Occupation? In a historiography dominated by the themes of genocide, statehood, migrations and the diaspora, there is hardly any place for books, and even less for libraries. However, their study sheds light on the structuring of an Armenian transnational space in the 20th century. It questions how writings and places might become national heritage in the frame of emigration. Finally, it allows us to explore the reconstruction of a sense of nation in exile, in a historical context shaped by annihilation and dispersion.